Local delivery of soluble fractalkine (CX3CL1) peptide restores ribbon synapses after noise-induced cochlear synaptopathy - Manickam, Vijayprakash; Maity, Sibaprasad; Murali, Sree Varshini; Gawande, Dinesh Y.; Stothert, Andrew R.; Batalkina, Lyudamila; Cardona, Astrid E.; Kaur, Tejbeer (Frontiers in Cellular Neuroscience, 2024)
Cochlear ribbon synapses between sensory inner hair cells (IHCs) and spiral ganglion neurons (SGNs) are vulnerable to rapid and primary damage and/or loss due to noise overexposure. Such damaged ribbon synapses can repair spontaneously in mouse and guinea pig. However, the mechanisms for synaptic repair are unclear. Previously, we have demonstrated a critical role for the fractalkine signaling axis (CX3CL1-CX3CR1) in synaptic repair, wherein noise-damaged ribbon synapses are spontaneously repaired in the presence of fractalkine receptor (CX3CR1) expressed by cochlear macrophages. Here, we examined whether local administration of chemokine fractalkine ligand (CX3CL1 or FKN) in the form of a peptide is effective in restoring synapses and hearing loss after noise-induced cochlear synaptopathy (NICS). Specifically, the efficacy of different isoforms of FKN was evaluated for restoration of loss of IHC ribbon synapses and hearing after NICS. A single transtympanic injection of soluble isoform of FKN (sFKN) peptide at 1 day after synaptopathic noise trauma for 2 hours at 93 decibel sound pressure level led to significant recovery of auditory brainstem response (ABR) thresholds, ABR peak I amplitudes and ribbon synapses in FKN knockout mice when compared to mice injected with membrane-bound FKN peptide (mFKN). Likewise, local treatment with sFKN peptide in FKN wild type mice restored synaptopathic noise-damaged ribbon synapses and ABR peak I amplitudes. Mechanistically, FKN regulates macrophage numbers in the damaged cochlea and in the absence of macrophages, sFKN failed to restore loss of synapses and hearing after NICS. Furthermore, sFKN treatment attenuated cochlear inflammation after NICS without altering the expression of CX3CR1. Finally, injected sFKN peptide was detectable inside the cochlea for 24 h localized to the basilar membrane and spiral lamina near the sensory epithelium. These data provide a proof-of-principle that local delivery of an immune factor, sFKN is effective in restoring ribbon synapses and hearing loss after NICS in a macrophage-dependent manner and highlights the potential of sFKN as an immunotherapy for cochlear synaptopathy due to noise.